2008
DOI: 10.1007/s00101-008-1402-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimierung des perioperativen Managements am Beispiel der laparoskopischen Leistenbruchoperation

Abstract: This study demonstrates that the length of stay after laparoscopic hernia repair can be reduced by one day by relatively simple means without affecting patient satisfaction or the complication rate. Most important is the introduction of clear-cut criteria that allow an early decision-making for discharge home. Moreover, many patients complain of constipation after laparoscopic surgery, and this may prolong the length of stay. This problem can be solved completely by the standardized use of sodium picosulfate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
1
0
4
Order By: Relevance
“…После операций небольшого объема на органах брюшной полости пикосульфат натрия профилактирует парез и восстанавливает нарушенную эвакуаторную функцию толстой кишки, что позволяет достигнуть более раннего отхождения газов и появления первого стула в послеоперационном периоде и благоприятно сказывается на самочувствии пациента, позволяя раньше выписать его на амбулаторное лечение [27,37].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…После операций небольшого объема на органах брюшной полости пикосульфат натрия профилактирует парез и восстанавливает нарушенную эвакуаторную функцию толстой кишки, что позволяет достигнуть более раннего отхождения газов и появления первого стула в послеоперационном периоде и благоприятно сказывается на самочувствии пациента, позволяя раньше выписать его на амбулаторное лечение [27,37].…”
Section: Discussionunclassified
“…Существует несколько исследований, анализирующих лечение послеоперационного пареза приемом пикосульфата натрия и его аналога предыдущего поколения бисакодила, и все они показали положительные результаты, что позволяет использовать их в периоперационном лечении, но из-за низкой доказательной базы требуется проведение дальнейших исследований в этой важной для хирургии теме, поскольку если эти наблюдения будут подтверждены, методика раннего опорожнения толстой кишки приемом стимулирующих слабительных найдет широкое применение в абдоминальной хирургии и других ее разделах [27,37].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Accordingly, the postoperative length of stay (including the day of surgery) was significantly reduced from 4.2 ± 0.6 to 3.3 ± 0.6 days. 17 Fixation of the mesh was done by secure strap in TEP 21 cases, nonfixation was done in 28 cases and in TAPP, fixation of the mesh was done in 23 cases, nonfixation was done in 26 cases; no recurrence occurs in fixed mesh. Contrary to our results, Craig Taylor et al found that mesh fixation appears to be unnecessary in TEP repair of small hernial defects.…”
Section: Discussionmentioning
confidence: 99%
“…Die Zunahme ambulanter Operationen und der Anspruch der Patienten auf eine schnelle sowie komplikationslose post operative Erholung physischer und psy chischer Funktionen erfordern Anäs thesietechniken, die eine zügige Wieder herstellung der Vigilanz ermöglichen [4,12]. Neben der Vermeidung postoperati ver Komplikationen wie Schmerzen, post operative Übelkeit und Erbrechen ("post operative nausea and vomiting", PONV) oder "shivering" ist auch die rasche Wie derherstellung einer ausreichenden Vi gilanz von großer Bedeutung.…”
Section: Hintergrund/fragestellungunclassified